Pitfalls of Frozen Section in Gynecological Pathology: A Rare Case of Ovarian Lymphoma in an HIV-Positive Woman Resembling Dysgerminoma on Frozen Section. (June 2019) - Wang, Qing; Rodriguez, Raul; Marcus, Jenna Z.; Podolsky, Lisa; Campbell, Damali; Heller, Debra
Primary lymphoma of the ovary, particularly in an HIV-positive woman, is exceptionally rare, and ovarian lymphoma may not be considered at the time of intraoperative consultation. In this article, we present a case in an HIV-positive woman thought to be a dysgerminoma at the time of frozen section, but which was found to be a diffuse large B-cell lymphoma of the ovary.